SCHOOL COOPERATION MANAGEMENT WITH DUDI IN INCREASING THE QUALITY OF GRADUATES - Tahshir , Tahshir (Managere: Indonesian Journal of Educational Management, 2022)
The focus of this research is to find out the cooperation management of SMKN 1 Padang Cermin with the industrial world in improving the quality of graduates and the benefits resulting from this collaboration. This research uses a qualitative descriptive research type. Data is obtained and then collected to be processed systematically. From the interview, clarifying, presenting, and concluding the data. The study results show that the management of school collaboration with the industrial world is good with the planning process carried out by SMKN 1 Padang Cermin conducting surveys and program analysis, preparing partnership proposals, and program development. Organizing process by detailing all the work that must be carried out to achieve organizational goals, distributing workloads, and developing mechanisms to coordinate the work of members of the organization. The process of implementing collaboration includes Curriculum Validation, Industrial Visits, Internships, Training Programs, UKK, Production Programs, Tools and Equipment Assistance, and Graduate Distribution Programs. Moreover, the process of controlling and evaluating activities for the Cooperation program carried out by SMKN 1 Padang Cermin with the Business and Industrial World (PT AHM) has been evaluated at the end of each year. From this collaboration, the benefits felt by the school and PT.AHM.